KAJIAN TEKNOLOGI FASADE PADA BANGUNAN KAMPUS UMN DI TANGERANG - Rahayu, Tuntun; Setiawan, Eko (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2020)
The UMN campus building is one of the buildings that has a very uniquefacade, which resembles an egg shell. The research method uses several stages thatcan help research, namely observing research objects in the area of the UMNcampus in Tangerang, the research tool uses a cellphone camera equipped withGPS, data collection techniques by observing and documenting the object ofresearch, data analysis techniques to analyze problems. This type of building in thedouble skin category has a double layer of metal material by applying a breathingwall with a pattern of holes of different sizes, which is useful for air circulation.Another material, glass material combined with double skin hole motif, glassmaterial is able to create patterned light shadows so that it looks memorable andnuanced